Pengabdian Kepada Masyarakat: Implementasi Program Setetes Air Sejuta Manfaat dalam Pembangunan Sumur Bor Masjid Al-Khair Perumahan Taman Bentiring Residence - Rezi Munizar; Rego Renaltin; Buyung Mantap (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The availability of clean water is a fundamental necessity that supports religious activities, sanitation, and community life. Al-Khair Mosque in Taman Bentiring Residence Housing, Bengkulu City, experienced limited access to clean water, affecting worship activities and religious social programs. The “One Drop of Water, Millions of Benefits” Community Service Program aimed to provide a sustainable clean water source through community-based borewell construction supported by public participation and philanthropic initiatives. The implementation method included field surveys, community outreach, fundraising, borewell construction, water installation, and program evaluation through observation, documentation, and interviews. The results showed that the program successfully improved access to clean water, enhanced the implementation of worship services, strengthened community participation, and fostered a culture of mutual cooperation in managing public facilities. This program demonstrates that collaboration among higher education institutions, mosque administrators, local communities, and donors can establish a sustainable community empowerment model that has the potential to be replicated in other areas facing similar challenges.